PEMBELAJARAN KOOPERATIF TIPE JIGSAW PADA MATA PELAJARAN IPS - ., Diana; Balkis, Syarifah (Makassar Journal of Social Sciences, 2013)
The aim of this study is ( 1 ) To determine the effectiveness of the jigsaw cooperative learning methods in improving learning outcomes in social studies classes SMP Negei 1 Balocci Pangkep through Jigsaw cooperative learning methods. ( 2 ) To know the factors supporting and inhibiting the implementation of the jigsaw cooperative method in SMP Negeri 1 Balocci Pangkep. The subjects were students of class VIII F which totaled 28 students. This study conducted two cycles, each cycle consisting of komponem action planning, action, observation and reflection. Data collection techniques are implemented tests student learning outcomes in quantitative analysis and observation sheet dianalisisi qualitativel. The results of the study are: The effectiveness of the jigsaw method of cooperative learning in improving student learning outcomes in social studies classes SMP Negeri 1 Balocci Pangkep is pretty good views of improving student learning outcomes, increase student attendance, cooperation, active and student attendance. Factors Supporting Cooperative Learning Method Jigsaw type is of that type of jigsaw learning model has a positive impact on teaching and learning activities, which can increase the activity of the teacher and the students during the learning , and to increase students' interest in participating in the next lesson